2015
DOI: 10.3920/wmj2014.1843
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetic study and oral bioavailability of deoxynivalenol in turkey poults, and comparative biotransformation between broilers and turkeys

Abstract: The aim of present study was to reveal the toxicokinetic properties and absolute oral bioavailability of deoxynivalenol (DON) in turkey poults. Six turkey poults were administered this Fusarium mycotoxin per os and intravenously in a two-way cross-over design. Based on non-compartmental analysis, DON was absorbed rapidly (Tmax = 0.57 h) but incomplete, as the oral bioavailability was only 20.9%. Deoxynivalenol was rapidly eliminated as well, both after oral (T1/2elimination PO = 0.86 h) as well as intravenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 25 publications
3
50
0
Order By: Relevance
“…In both chicken (Osselaere et al 2013) and turkey (Devreese et al 2015) the DON absorption was low as reflected by the AUC po,plasma, norm = 0.03 l (h*kg) -1 . On the contrary, the absorption appears to be higher in piglets (Prelusky et al 1988) and pigs (Goyarts & Dänicke 2006) as shown by AUC po,plasma,norm = 4.4 and 2.3 l (h*kg) -1 , respectively.…”
Section: Toxicokinetics Of Donmentioning
confidence: 99%
“…In both chicken (Osselaere et al 2013) and turkey (Devreese et al 2015) the DON absorption was low as reflected by the AUC po,plasma, norm = 0.03 l (h*kg) -1 . On the contrary, the absorption appears to be higher in piglets (Prelusky et al 1988) and pigs (Goyarts & Dänicke 2006) as shown by AUC po,plasma,norm = 4.4 and 2.3 l (h*kg) -1 , respectively.…”
Section: Toxicokinetics Of Donmentioning
confidence: 99%
“…The absolute oral bioavailability (F) of DON is slightly higher (30%) in fasted pigeons compared to fasted broiler chickens (19%) and turkeys (21%) [7, 8]. However, this low F suggests that intestinal epithelial cells are exposed to significant DON concentrations which eventually may affect intestinal translocation and colonization of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis was based on a method for turkeys and broiler chickens, as previously described by Devreese et al . [7]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations